Resepsi Wahyu Dunung Raharjo Dalam Pertunjukan Wayang Pamarta Lakon Katresnan-ku Tanpa Wates Dari Kitab Injil - Widawati, Seruni (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2024)
Wayang has a history related to part of the worship ritual of a particular belief or religion. It turns out that currently wayang is still used by the Christian community which then makes wayang that is specifically created to spread religious values, namely to proclaim the teachings of Christ. One of the wayang used for the preaching of Christianity is Wayang Pamarta. The Lakon chosen in this study is Katresnan-Ku Tanpa Wates by Wahyu Dunung Raharjo. This lakon is very interesting because it is a new lakon adapted from the Gospels of Matthew, Mark, Luke, and John then realized into a wayang performance using the concepts of garap pakeliran. The purpose of this study is to examine the aesthetic reception carried out by the creator to reveal the reader’s response to the Gospel, in this case Wahyu Dunung Raharjo with an active reaction applied to the wayang pamarta performance. This study uses a qualitative method with a sanggit approach and active reception. The results of the sanggit analysis were then re-analyzed with the concepts underlying the creation or arrangement of lakon wayang by Sumanto, namely: tutug, mulih, and kempel. The lakon Katresnan-Ku Tanpa Wates is the result of ‘reading’ or ‘receiving’ a sermon delivered by Pastor Petrus Agung, then undergoing a thought process until it is realized into a work of art of wayang pamarta performance. This process is carried out by interpreting sources and then producing sanggit by adding, subtracting, and innovating. The tutug criterion is reflected in the completion of the lakon events. The mulih criterion is seen in all the problems faced by the main character being resolved. The kempel criterion is seen in the intertwining of the problems of some characters presented in the lakon Katresnan-Ku Tanpa Wates.